Perceptions of Climate Variability among Smallholder Cocoa Farmers in Ghana - Amoako, Prince Kwadwo; Tham-Agyekum, Dr. Enoch Kwame (International Journal on Food, Agriculture and Natural Resources, 2025)
This study assessed smallholder cocoa farmers' perceptions of climate variability in Ghana. Through a survey of 600 farmers, findings indicate awareness of climate changes, particularly in temperature, while perceptions of variability in rainfall and other climate variables were more neutral. Farmers identified deforestation and agrochemical use as key drivers of climate variability. The study emphasizes the necessity for targeted interventions to enhance awareness and adaptive capacity among farmers by recommending comprehensive adaptation strategies and equitable resource access. These insights aim to inform policymakers and stakeholders to promote sustainable cocoa production in Ghana.